Hydro-catalytic treatment of organoamine boranes for efficient thermal dehydrogenation for hydrogen production - Coskuner, Ozge; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study aims to present the hydro-catalytic treatment of organoamine boranes for efficient thermal dehydrogenation for hydrogen production. Organoamine boranes, methylamine borane (MeAB), and ethane 1,2 diamine borane (EDAB), known as ammonia borane (AB) carbon derivatives, are synthesized to be used as a solid-state hydrogen storage medium. Thermal dehydrogenation of MeAB and EDAB is performed at 80 degrees C, 100 degrees C, and 120 degrees C under different conditions (self, catalytic, and hydro-catalytic) for hydrogen production and compared with AB. For this purpose, a cobalt-doped activated carbon (Co-AC) catalyst is fabricated. The physicochemical properties of Co-AC catalyst is investigated by well-known techniques such as ATR/FT-IR, XRD, XPS, ICP-MS, BET, and TEM. The synthesized Co-AC catalyst obtained in nano CoOOH structure (20 nm, 12% Co wt) is formed and well-dispersed on the activated carbon support. It has indicated that Co AC exhibits efficient catalytic activity towards organoamine boranes thermal dehydrogenation. Hydrogen release tests show that hydro-catalytic treatment improves the thermal dehydrogenation kinetics of neat MeAB, EDAB, and AB. Co-AC catalyzed hydro-treatment for thermal dehydrogenation of MeAB and EDAB acceleras the hydrogen release from 0.13 mL H-2/min to 46.12 mL H-2/min, from 0.16 mL H-2/min to 38.06 mL H-2/min, respectively at 80 degrees C. Moreover, hydro-catalytic treatment significantly lowers the H-2 release barrier of organoamine boranes thermal dehydrogenation, from 110 kJ/mol to 19 kJ/mol for MeAB and 130 kJ/mol to 21 kJ/mol for EDAB. In conclusion, hydro and catalytic treatment presents remarkable synergistic effect in thermal dehydrogenation and improves the hydrogen release kinetics. (C) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Organoamine boranes; Hydrogen; Storage; Solid-state; Activated carbon; AMMONIA BORANE; EXPERIMENTAL INSIGHTS; DIMETHYLAMINE-BORANE; NANOPARTICLES; HYDROTHERMOLYSIS; DECOMPOSITION; EVOLUTION; BORON; WATER; Chemistry; Electrochemistry; Energy & Fuels